Altitude-dependent climate impacts and economic feasibility of alternative fuels in aviation from 2025 to 2050 - Qiang Cui; Xu-jie Sun; Xing-yu Tang; Ying Zhou; Yu-xin Zhang; Ye Li (iScience)
Summary: The aviation industry plays an increasing role in climate change due to emissions at cruise altitudes. This study combines projections from the Aviation Integrated Model (AIM) and simulations from the Aviation-FAIR model to assess greenhouse gas concentrations, radiative forcing, and temperature effects across emission altitudes from 500 to 40,500 ft during 2025–2050. The results reveal that climate impact intensifies with altitude and peaks at 34,500 ft. In addition, a cost-benefit analysis evaluates the use of sustainable aviation fuel (SAF) and hydrogen energy in civil aviation. By 2050, offsetting the costs of these fuels will require $354.44 billion for SAF and $1,888.44 billion for hydrogen. This study assesses the altitude-dependent climate effects of aircraft emissions and the economic feasibility of alternative aviation energy technologies, highlighting both their mitigation potential and cost-related limitations.